Effect of lanthanum substitution on microstructure and electrical properties of (Bi0.5Na0.5)1-1.5x Lax Ti0.41Zr0.59O3 ceramics - Jaiban P. (2014)
Bismuth sodium zirconate (BNZ) based ceramics with a composition of (Bi0.5Na0.5)1-1.5x Lax Ti0.41Zr0.59O3 where x = 0, 0.005, 0.01, 0.02 and 0.03 were prepared by a solid-state mixed oxide method and sintered at the temperature of 900 °C for 2 h. All the samples had relative density between 91 and 97% of their theoretical values. Phase analysis using X-ray diffraction indicated single rhombohedral or pseudo-cubic perovskite structure. SEM showed that addition of La caused the average grain size of the BNTZ ceramics to decrease as well as an improvement of sample density. Dielectric properties at room temperature measured at 10 kHz indicated that addition of La increased the dielectric constant. The results of ferroelectric characterization also revealed that adding La caused a decrease in coercive field without affecting the remanent polarization. © 2011 Elsevier Ltd and Techna Group S.r.l.